Quantitation of left ventricular asynchrony on radionuclide angiography phase images - Alfano, B; Betocchi, S; Pace, L; Perrone-Filardi, P; Chiariello, M; Salvatore, M (European journal of nuclear medicine, 1990)
Quantitation of left ventricular (LV) asynchrony is relevant in clinical cardiology, as well as in evaluating LV mechanical properties. Radionuclide angiography (RA) phase images are extensively used, and asynchrony is usually assessed by computing the standard deviation of phase angle distribution (SD). However, SD is dependent on count statistics and does not take into account the spatial distribution of asynchrony. In this study a new index to evaluate asynchrony on phase images is presented (differential uniformity parameter, DUP). DUP is based on the frequency analysis of phase images. Diagnostic accuracy and reproducibility of either SD or DUP were tested. Reproducibility was evaluated in 15 patients studied by RA twice within a few minutes. DUP showed a better reproducibility than SD. Diagnostic accuracy was estimated in 84 patients, divided into four subgroups on the basis of coronary arteriography and contrast ventriculography findings: (a) 25 control subjects, (b) 16 patients with coronary artery disease (CAD) and normal LV wall motion, (c) 23 patients with CAD and LV hypokinesia and (d) 20 patients with CAD and LV dyskinesia. Relative diagnostic ability was assessed by comparing the areas under receiver-operating characteristic curves. DUP's area was larger than SD's when group D was tested against all the other groups (DUP's area = 87% +/- 5%, SD's area = 76% +/- 7%; P less than 0.01). Thus, our study indicates that DUP is more reproducible and more accurate than SD in identifying patients with CAD and LV dyskinesia.